التكييف الفقهي للوصية بالعضو الإنساني - زاهر, فارس; قدومي, شادي (University of Eloued جامعة الوادي, 2018)
ملخص: إن موضوع التبرع بالأعضاء الآدمية بأبعاده المعاصرة من أجل غرسها، موضوع حساس لأنه يتصل بالأحياء والأموات، خاصة مع الطفرة النوعية التي عرفها الطب وعلم الجراحة في العشرين عامًا الماضية مما فتح آفاقًا جديدة في هذا الميدان، والتي منها مسألة الوصية من أجل التبرع بالعضو البشري، وهي مسألة مستجدة ولا يتوقع أن يكون الفقهاء قديما قد تعرضوا لبحث حكمها الشرعي، ومن هذا المنطلق ارتأينا أن نعرض موقف فقهاء المسلمين حول مسألة الوصية بأعضاء الآدمي حال حياته لما بعد مماته. Abstract: Human organs donation for transplantation (with its modern perspectives) is a very sensitive subject due to its direct relation with both the dead and the living, and especially with the revolutionary advancement that the medical science had achieved in the last twenty years. As a result, new subjects of discussion made appearance. The will to donate organs is one of these subjects, and it is not expected that old scholars had had a chance to make researches about it according to Islamic law. Starting from this, we wanted to present the views of different Muslim scholars about making a will to donate organs after the death of a person. ا
مقال بمجلة الشهاب
Keywords: الكلمات المفتاحية: الوصية؛ التبرع؛ العضو الإنساني؛ زرع الأعضاء; Commandment; Donation; Humanitarian Member; organ transplant.